THE ROLE OF GLOBAL IMBALANCES IN THE FORMATION OF THE GLOBAL FINANCIAL MARKET ASSETS DIVERSIFICATION TREND - ELENA ANATOL’EVNA Zvonova (Мир новой экономики, 2018)
The article analyzes the role of global imbalances, the global financial architecture in the formation of the modern imperative trend of diversification of financial asset markets. The article subject covers the study of statistical data on the state and trends of the major groups of financial assets of international and national financial markets (NFM). The objective is to identify the main problems and development directions of the global financial market in the conditions of global imbalances. The work carries out the processing of statistical data that allowed to give the quantitative characteristics of the main types of financial assets and their role in the evolution of the global financial market. The methods used for study are those of comparative analysis, synthesis,integrated approach, system and other methods of cognition. It was concluded that due to the broad diversification of financial assets in the post-crisis period, the key objects of reform global financial architecture are its following institutions: the banking sector; financial market in the broadest sense, especially its equity sector and derivatives sector; non-bank financial institutions; credit ratings and rating agencies